PENGARUH PENERAPAN ARTIFICIAL INTELLEGENCE PADA KEHIDUPAN MASYARAKAT DI INDONESIA - Mustofa, Zamzam; Arifatuzzahro, Aulia; nazira, Arni; Wahyuni, Ruslina Dwi; Mukminin, Amir (Lisyabab : Jurnal Studi Islam dan Sosial, 2023)
Technology is very important in the 4.0 revolution era in this industrial sector. The impact of technology on human life cannot be overstated. The emergence of technology brings several changes. Technological developments can be seen to go hand in hand with the development of time. The field of science and technology is always advancing and innovating rapidly, as seen from the technical breakthroughs that have been made. Rapid technological advances impact human existence and enable rapid social transformations that often occur without our even realizing it. Artificial intelligence is one of the technical advances that has the greatest potential impact. For the purpose of finding a solution to a challenge, a technology known as artificial intelligence (often referred to as AI) is used to replicate the intelligence of living and inanimate organisms. The use of artificial intelligence has an impact on human existence in various contexts. The purpose of this essay is to investigate how the use of artificial intelligence in Indonesia contributes to the ongoing transformation of society in this country. Library research is the approach used in this study. Literature research is a methodology for collecting data that involves completing a review study of books, literature, notes, and reports that are related to the problem being addressed. Researchers will read as much relevant literature as possible to collect as much data as possible in their search for hypotheses. Books, journals, periodicals, research results (theses and dissertations), and other acceptable sources such as newspapers, the internet, and other sources can all be considered library resources. Keywords: Technology, Artificial Intelligence, Social Change